2021
DOI: 10.1186/s12889-021-11240-7
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of the current status and associated factors of tuberculosis knowledge, attitudes, and practices among elderly people in Shenzhen: a cross-sectional study

Abstract: Background The incidence and risk of tuberculosis (TB) among the elderly population have increased with the ageing population in China. This study aimed to assess the current status and associated factors of TB knowledge, attitudes, and practices among elderly people in Shenzhen City, China, which may provide references for the development of TB prevention and treatment policies targeting elderly people. Methods A multistage random sampling method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 10 publications
0
12
1
2
Order By: Relevance
“…In order to avoid the problem of collinearity among influencing factors, the variance inflation factor was used for diagnosis ( 16 ). Multiple stepwise regression analysis was performed using the backward entry method with the exclusion criterion of α out = 0.10 ( 17 ). Stata15.0 was used for data collation and analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In order to avoid the problem of collinearity among influencing factors, the variance inflation factor was used for diagnosis ( 16 ). Multiple stepwise regression analysis was performed using the backward entry method with the exclusion criterion of α out = 0.10 ( 17 ). Stata15.0 was used for data collation and analysis.…”
Section: Methodsmentioning
confidence: 99%
“…A recent cross-sectional study conducted among older adults in Shenzhen, China, reported that > 70% of the respondents were aware of TB as a contagious disease, its symptoms, and preventive measures. Yet, less than half knew that TB was curable, and only one-third were willing to be screened for TB if they were to develop suspicious symptoms [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are 9 epidemiological studies included in this review from the database search of PubMed [4][5][6][7][8][9][10][11][12]. They are summarized in the Table The studies included in this review revealed the following outcomes:…”
Section: Resultsmentioning
confidence: 99%
“…A study [6] used a multi-stage sampling method to conduct a questionnaire survey on the current status of knowledge, attitudes, and behaviors regarding tuberculosis among 1078 elderly adults in Baoan District, Shenzhen, China, and found that elderly adults with low education and high per capita household income had a lower rate of knowledge about tuberculosis and poorer awareness of attitudes and behaviors. The early symptoms of TB are atypical and easily ignored, and many elderly people are also unaware of the national policy of free TB treatment and are reluctant to go to the clinic for fear of adding a burden to their children, all of which contribute to the delay in consultation and add to the burden of TB treatment in the elderly [24].…”
Section: Resultsmentioning
confidence: 99%